Hyperglycemia related to high-dose glucocorticoid use in noncritically ill patients - González González, José Gerardo; Mireles Zavala, Leonor Guadalupe; Rodríguez Gutiérrez, René; Gómez Almaguer, David; Lavalle González, Fernando Javier; Tamez Pérez, Héctor Eloy; González Saldívar, Gerardo; Villarreal Pérez, Jesús Zacarías (2013)
Background: Glucocorticoids commonly cause drug-induced diabetes. This association is well recognized but available evidence does not answer clinically relevant issues in subjects without diabetes. Methods: Thirty-five individuals without diabetes with a recent diagnosis of acute lymphoblastic leukemia or nonHodgkin’s lymphoma on high-dose glucocorticoid therapy were studied. Close systematic monitoring of fasting and postprandial glycemia and fasting insulin determinations, HOMA-insulin resistance and HOMA β-cell function were performed. The primary objective was to define the incidence of secondary diabetes in patients treated with highdose glucocorticoids. Secondary objectives were to specify the intensity, the moment it appears and the evolution of hyperglycemia, in addition to the risk factors, mechanisms and impact of continuous and cyclical glucocorticoids on the development of hyperglycemia. Results: Mean age of patients was 38.4 ± 18.7 years. The incidence of diabetes was 40.6% and was found after the first week; half the time it occurred between the second and fourth. Two-thirds spontaneously normalized by eight weeks. Continuous glucocorticoid administration had a higher incidence of fasting hyperglycemia (P = 0.003). Mean peak insulin levels were significantly higher in cases of diabetes. Conclusions: High-dose prednisone for 2 to 3 months produced an elevated incidence of diabetes, usually with mild hyperglycemia occurring between the second and fourth week, normalizing spontaneously in all cases. Hyperglycemia was more frequent with continuous doses and occurred in cases with increased insulin resistance. The clinical and therapeutic characteristics of our participants, who were otherwise healthy, could represent the clinical setting of many patients with illness from other medical areas that might require high doses of GC for six to twelve weeks.